PERANCANGAN SISTEM ADMINISTRASI PRODUKSI DAN GUDANG BERBASIS VB.NET DI UD. HASIBUAN JAMES PLYWOOD KARAWANG - Rani Laple Satria Putra; Dea Andini Andriati; R. Wahyudi Darmawan (KH. A. Wahab Hasbullah University, 2021)
This production and warehouse administration system was created to facilitate UD's work. Hasibuan James Plywood Karawang employee in managing production and warehouse data. Data management system at UD. Hassibuan James Plywood Karawang still uses the manual method and is not yet computerized. Data storage still uses reports stored in Ms. Excel. Storage using Ms. Excel is less effective because it is not a database system and is not centralized, so it is necessary to design a system that uses a database so that data storage can be centralized. The result is the creation of this administrative system that can be used to input production data, products come out of the warehouse and monitor inventory conditions in the warehouse. This study also explains that the use of a computerized information system based on Visual Basic. Net can increase employee productivity, make it easier to access the data needed and become more effective and efficient.